KESANTUNAN BERBAHASA DALAM INTERAKSI PEMBELAJARAN BAHASA INDONESIA DI SMPN SATU ATAP 1 BALIK BUKIT KABUPATEN LAMPUNG BARAT - Surastina Surastina (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
This research is focused on the issue of the politeness principle of language in One Roof One State High School, Balik Bukit, which was studied pragmatically. Data obtained using the method of referring to the SBLC technique (see free engraved capable), record techniques, and note techniques. The results of the study indicate the following points. (1) Types of deviations in the language politeness principle consist of single deviations and double deviations. Single deviations include deviations of wisdom maxim, maxim of generosity, maxim of praise, maxim of humility, maxim of agreement, and maxim of sympathy. Dual deviations include deviations of wisdom maxim and generosity maxim, wisdom maxim and wisdom maxim, generosity maxim and praise maxim, praise maxim and agreement maxim, modesty maxim and sympathy maxim, sympathy maxim and sympathy maxim, wisdom maxim, generosity, and maxim maxim and maxim of praise, maxim of modesty, and maxim of agreement. (2) The cause of deviations in the politeness principle of language is caused by the speaker intentionally accusing the interlocutor, deliberately speaking out of context, protective of opinions, encouraging emotion of the speaker, direct criticism with harsh words, and mocking.